Neuropsychological changes following deep brain stimulation surgery for Parkinson's disease: comparisons of treatment at pallidal and subthalamic targets versus best medical therapy. Issue 6 (2nd September 2014) - Rothlind, Johannes C; York, Michele K; Carlson, Kim; Luo, Ping; Marks, William J; Weaver, Frances M; Stern, Matthew; Follett, Kenneth; Reda, Domenic
Abstract : Background: Deep brain stimulation (DBS) improves motor symptoms in Parkinson's disease (PD), but questions remain regarding neuropsychological decrements sometimes associated with this treatment, including rates of statistically and clinically meaningful change, and whether there are differences in outcome related to surgical target. Methods: Neuropsychological functioning was assessed in patients with Parkinson's disease (PD) at baseline and after 6 months in a prospective, randomised, controlled study comparing best medical therapy (BMT, n=116) and bilateral deep brain stimulation (DBS, n=164) at either the subthalamic nucleus (STN, n=84) or globus pallidus interna (GPi, n=80), using standardised neuropsychological tests. Measures of functional outcomes were also administered. Results: Comparison of the two DBS targets revealed few significant group differences. STN DBS was associated with greater mean reductions on some measures of processing speed, only one of which was statistically significant in comparison with stimulation of GPi. GPi DBS was associated with lower mean performance on one measure of learning and memory that requires mental control and cognitive flexibility. Compared to the group receiving BMT, the combined DBS group had significantly greater mean reductions at 6-month follow-up in performance on multiple measures of processing speed and working memory. After calculating thresholds for statistically reliable change from data obtained from the BMT group, the combined DBS group also displayed higher rates of decline in neuropsychological test performance. Among study completers, 18 (11%) study participants receiving DBS displayed reliable decline by multiple indicators in two or more cognitive domains, a significantly higher rate than in the BMT group (3%). This multi-domain cognitive decline was associated with less beneficial change in subjective ratings of everyday functioning and quality of life (QOL). The multi-domain cognitive decline group continued to function at a lower level at 24-month follow-up. Conclusions: In those with PD, the likelihood of significant decline in neuropsychological functioning increases with DBS, affecting a small minority of patients who also appear to respond less optimally to DBS by other indicators of QOL. Trial registration number: NCT00056563 and NCT01076452 .